Risk assessment of dietary factors in global pattern of ischemic heart disease mortality and disability-adjusted life years over 30 years - Wang, Fang; Mubarik, Sumaira; Zhang, Yu; Shi, Wenqi; Yu, Chuanhua (Frontiers in Nutrition, 2023)
Objectives To investigate differences in the burden of ischemic heart disease (IHD) related mortality and disability-adjusted life years (DALYs) caused by dietary factors, as well as the influencing factors with age, period, and cohort effects, in regions with different social-demographic status from 1990 to 2019. Methods We extracted data on IHD mortality, DALYs, and age-standardized rates (ASRs) related to dietary risks from 1990 to 2019, as IHD burden measures. Hierarchical age-period-cohort analysis was used to analyze age and time related trends, and the interaction between different dietary factors on the risk of IHD mortality and DALYs. Results Globally, there were 9.2 million IHD deaths and 182 million DALYs in 2019. Both the ASRs of death and DALYs declined from 1990 to 2019 (percentage change: -30.8% and -28.6%, respectively), particularly in high and high-middle socio-demographic index (SDI) areas. Low whole grains, low legumes, and high sodium diets were the three main dietary factors that increased the risk of IHD burden. Advanced age[RR (95%CI):1.33(1.27,1.39)], male [1.11(1.06,1.16)] were independent risk factors for IHD mortality worldwide, and in all SDI regions. After controlling for age effects, IHD risk showed a negative period effect overall. Poor diets were positively associated with increased risk of death, but not yet statistically significant. Interactions between dietary factors and advanced age were observed in all regions after adjusting for related variables. In people aged 55 and above, low intake of whole grains was associated with an increased risk of IHD death [1.28(1.20,1.36)]. DALY risks showed a similar but more obvious trend. Conclusion IHD burden remains high, with significant regional variations. The high IHD burden could be attributed to advanced age, gender (male), and dietary risk factors. Dietary habits in different SDI regions may have varying effects on the global burden of IHD. In areas with lower SDI, it is recommended to pay more attention to dietary problems, particularly in the elderly, and to consider how to improve dietary pattern in order to reduce modifiable risk factors.